Homogeneous photoelectrochemical biosensing via synergy of G-quadruplex/hemin catalysed reactions and the inner filter effect. Issue 12 (17th January 2020) - Song, Xin; Hou, Ting; Lu, Fangfang; Wang, Yuze; Liu, Junjie; Li, Feng
Abstract : We develop a label-free homogeneous photoelectrochemical biosensing strategy for microRNA quantification based on the synergy of G-quadruplex/hemin catalyzed electron donor consumption and the inner filter effect. Abstract : We developed a label-free homogeneous photoelectrochemical biosensing strategy based on the synergy of G-quadruplex/hemin catalysed electron donor consumption and the inner filter effect for highly selective and sensitive microRNA assay.